Pengaruh Overtime dan Overwork terhadap Employee Performance Dimediasi oleh Perceived Compensation - Sitanggang, Karunia Angel Febiola; Ariadi, Gede (Jurnal Maksipreneur, 2025)
This research aimed to determine the impact of overtime and overwork on employee performance, as mediated by perceived compensation. Conducted at a medical equipment distributor in Bali, the study surveyed all 100 permanent employees using a census method. Data were collected via an online questionnaire and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results indicated that: (i) overwork positively affects employee performance, while overtime does not; (ii) perceived compensation fully mediates the effect of overtime on employee performance, but not the effect of overwork.